pH stimuli-responsive hydrogels from non-cellulosic biopolymers for drug delivery - Vegad, Udaykumar; Patel, Megha; Khunt, Dignesh; Zupančič, Ožbej; Chauhan, Sanjay; Paudel, Amrit (Frontiers in Bioengineering and Biotechnology, 2023)
Over the past several decades, there has been significant growth in the design and development of more efficient and advanced biomaterials based on non-cellulosic biological macromolecules. In this context, hydrogels based on stimuli-responsive non-cellulosic biological macromolecules have garnered significant attention because of their intrinsic physicochemical properties, biological characteristics, and sustainability. Due to their capacity to adapt to physiological pHs with rapid and reversible changes, several researchers have investigated pH-responsive-based non-cellulosic polymers from various materials. pH-responsive hydrogels release therapeutic substances in response to pH changes, providing tailored administration, fewer side effects, and improved treatment efficacy while reducing tissue damage. Because of these qualities, they have been shown to be useful in a wide variety of applications, including the administration of chemotherapeutic drugs, biological material, and natural components. The pH-sensitive biopolymers that are utilized most frequently include chitosan, alginate, hyaluronic acid, guar gum, and dextran. In this review article, the emphasis is placed on pH stimuli-responsive materials that are based on biological macromolecules for the purposes of drug administration.